The Effect Of Product Difference on Consumer Satisfaction of Toyota Avanza Car Users at PT. Hadji Kalla Alauddin Branch, Makassar City - Sarah Bahar; Muh Nur Yamin; Maya Kasmita (Public Resource Innovation Management and Excellence, 2024)
This study aims to determine the effect of product differentiation on consumer satisfaction of Toyota Avanza car users at PT Hadji Kalla Alauddin Makassar City Branch. This research uses quantitative methods. Data collection techniques in this study using observation and questionnaires. The population in this study was 844 people. The sampling method used is the Krejcie table with a sample of 243 respondents. The data obtained from the research results were processed using linear regression data analysis and the use of the SPSS 25 application which consists of validity and reliability tests. Descriptive data analysis techniques and inferential stratistic analysis. The results of the study based on (t test) showed that product differences had a significant effect on consumer satisfaction with a significance value of 0.000 <0.05. Determinant Coefficient test results obtained R Square of 0.457. This shows that the dependent variable of customer satisfaction of 45.7% is influenced by the independent variable of product differentiation, while the rest is influenced by other factors not included in this study. It can be said that product differentiation, in other words, the company must develop much better product differentiation if it is to continue to benefit from customer satisfaction.